Adenosine stress perfusion cardiac magnetic resonance imaging in patients undergoing intracoronary bone marrow cell transfer after ST-elevation myocardial infarction: the BOOST-2 perfusion substudy - Seitz, Andreas; Chorianopoulos, Emmanuel; Katus, Hugo (Clinical research in cardiology, 2020)
In the placebo-controlled, double-blind BOne marrOw transfer to enhance ST-elevation infarct regeneration (BOOST) 2 trial, intracoronary autologous bone marrow cell (BMC) transfer did not improve recovery of left ventricular ejection fraction (LVEF) at 6 months in patients with ST-elevation myocardial infarction (STEMI) and moderately reduced LVEF. Regional myocardial perfusion as determined by adenosine stress perfusion cardiac magnetic resonance imaging (S-CMR) may be more sensitive than global LVEF in detecting BMC treatment effects. Here, we sought to evaluate (i) the changes of myocardial perfusion in the infarct area over time (ii) the effects of BMC therapy on infarct perfusion, and (iii) the relation of infarct perfusion to LVEF recovery at 6 months.
Published online: 10 August 2019
Gesehen am 02.07.2020